Correlation Analysis in Software Information Dissemination Testing in Regional Apparatus Organizations (RAD) to Support Jogja Smart City - Hero Wintolo; Sudaryanto Sudaryanto; Friska Ayu Dhawara (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
The application of information technology is one of the characteristics of smart cities that are used to provide services for their citizens. This application does not only change what previously did not use information technology to use information technology but the uses of software that is specifically used to serve the community so that the service process becomes fast as is done in the Regional Government RAD (Pemda) of Yogyakarta City. Before using a special application, dissemination services were performed using Microsoft Excel which can only be accessed on a computer. The software for information dissemination was tested by distributing questionnaires with questions grouped on Service quality improvement for information dissemination and User satisfaction. The results were processed and analyzed using the correlation method. The result showed a value of sig.(2-tailed) is 0,000, the Correlation Coefficient of 0,400, so it can be concluded that the relationship between improving service quality for information dissemination on RAD and user satisfaction is significant, strong enough, and unidirectional.